The Effect of Visual Learning Style and Critical Thinking Ability on Learning Outcomes of Islamic Education Students Batch 2022 Faculty of Tarbiyah and Keguruan at UIN Alauddin Makassar - Asep Wijaya; Muhammad Yaumi; Besse Marjani Alwi (Universitas Muhammadiyah Enrekang, 2024)
The aims of this research are: 1) Analyze the influence of learning styles on the learning outcomes of PAI students in the class of 2022 at the tarbiyah and teacher training faculty at UIN Alauddin Makassar, 2) Analyze the influence of critical thinking on the learning outcomes of PAI students in the class of 2022 at the tarbiyah and teacher t[]aining faculty at UIN Alauddin Makassar, 3) Analyze the influence of learning styles and critical thinking on the learning outcomes of PAI students in the class of 2022, tarbiyah and teacher training faculty at UIN Alauddin Makassar. This research method uses quantitative, this type of research is ex post facto and uses a pedagogical approach. The sample in this research was PAI students class of 2022 who were obtained using a sampling technique, namely the saturated sampling technique. The number of samples in the 2022 PAI class is 56 students. To collect data using learning style questionnaire instruments and critical thinking questionnaires. Research data was analyzed using descriptive data analysis and multiple linear regression analysis or using the t test and f test. The results of descriptive analysis on the visual learning style variable obtained an average value of 51.61, which means the medium category and critical thinking obtained an average value of 42.21, which means the medium category while learning outcomes obtained an average value of 3.78, which means the medium category. Based on the results of data analysis, the coefficient table shows that visual learning style influences learning outcomes with a sig of 0.001. Critical thinking influences learning outcomes with a sig value of 0.001. In the multiple regression test, the ANOVA results found that visual learning style and critical thinking both had an influence on learning outcomes with a value below 0.005, namely 0.001. The implication of this research is that existing stakeholders can improve students' critical thinking and pay attention to dominant learning styles so that they can improve student learning outcomes